Popliteal pterygium syndrome: Orofacial and general features - S K Bahetwar; R K Pandey; T S Bahetwar (Wolters Kluwer Medknow Publications, 2011)
This report describes the case of a 13-year-old Indian boy with popliteal pterygium syndrome. The popliteal pterygium syndrome is an extremely rare hereditary disorder thought to occur with an incidence of approximately 1 in 300000 live births. It is a congenital malformation syndrome affecting the face, limbs, and genitalia with highly characteristic features, including popliteal webbing, cleft palate (with or without cleft lip), lower lip pits, syndactyly, and genital and nail anomalies. This patient was referred to our department because of complaints of pain in the mouth and poor oral health. The orofacial findings included cleft lip, cleft palate, lower lip pits, a few missing teeth, and severely decayed teeth. In this syndrome, the orodental problems are overshadowed by the major syndromic manifestations but nevertheless need appropriate management. These patients have special dental needs and early diagnosis of the affected children is therefore important in order to initiate preventive dental care and carry out appropriate dental treatment at the optimal time.